KAJIAN PROGRAM KONSELING PRANIKAH UMAT HINDU DALAM PERSPEKTIF KOMUNIKASI INTERPERSONAL DI PARISADA HINDU DHARMA INDONESIA DKI JAKARTA - wayan julianto; Untung Suhardi; I Made Jaya Negara Suarsa Putra (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2021)
ABSTRACTThis thesis will discuss about Premarital Counseling of Hindus as part of the Parisada Hindu Dharma Indonesia DKI Jakarta program for the purpose of providing services to foster pre-marital couples. However, today a marriage which is a sacred and sacred bond in which a pre-marital couple does not yet have a family meaning, because it is based on love without any preparation that will lead to the development of family life, needs equipping in accordance with marital administration information, about knowledge religion and responsibilities and responsibilities as Citizens. Hindu Premarital Counseling Study Program in the Perspective of Interpersonal Communication Parisada Hindu Dharma Indonesia DKI Jakarta. This study uses descriptive qualitative methods by collecting data through interviews, observations and documentation studies, then in this study using the theory of Phenomenology and Symbolic Interactionism. The findings of this study are that premarital counseling is not only limited to coaching, which is approved by PHDI DKI Jakarta, through this program creating superior and new programs that can be implemented first in DKI Jakarta by making marriage books and pre-marital module books. In addition, this couple also discussed about different education, very different, and very interesting. In addition, the couple was also interested in various programs that existed after the ceremony. This is a special drilling and offering program for religious people. Keywords: Hindu Premarital Counseling Program, DKI Jakarta of PHDI, Interpersonal Communication Perspectiv